Evaluating the Synergistic Potency of Essential Oils and Antibiotics Against Klebsiella pneumoniae BLSE Strains: Essential Oils and Antibiotics Against K. pneumoniae - Bariz, Karim; Trabelsi, Lamia; Lahcene, Souad; Salem-Bekhit, Mounir M.; Elossaily, Gehan M.; Ali Alzahrani, Hayat; Alharbi, Omar O.; Abbaci, Mohamed; Abbaci, Hocine; Benguerba, Yacine; Houali, Karim (Cellular and Molecular Biology, 2023)
Klebsiella pneumoniae producing extended-spectrum β-lactamases (ESBL) continues to pose huge therapeutic challenges in the treatment of infections, primarily urinary infections, due to its multidrug resistance to antibiotics. Therefore, there is a need for research on this topic to investigate ways to reduce the spread of antibiotic resistance, identify novel therapeutic approaches to treat these infections and gain a better understanding of the mechanisms of resistance. In this context, this study aimed to analyze the chemical composition of essential oils (EOs) of Thymus algeriensis, Syzygium aromaticum, and Eucalyptus globulus and assess their activity against K. pneumoniae ESBL strains, as well as the interaction type between these EOs and antibiotics used for the treatment of K. pneumoniae ESBL infections. The composition of the EOs was determined by gas chromatography-mass spectrometry (GC-MS). The activity of EOs was tested using the disc diffusion and liquid microdilution methods. The type of interaction between EOs and antibiotics was studied using the agar disk diffusion and chessboard methods. The analysis of the EO of T. algeriensis showed that the main compounds were thymol (23.14%), linalool (18.44%), and p-cymene (16.17%). The main constituents of EO of E. globulus were eucalyptol (54.29%), α-pinene (17.32%), aromadendrene (7.02%), and pinocarveol (6.32%). As for the EO of S. aromaticum, the major constituents were eugenol (80.46%) and eugenol acetate (16.23%). Results of the activity tests showed that all three EOs were active against the tested strains, with inhibition diameters ranging from 7.39±0.44mm to 32.4±1.05mm and minimum inhibitory concentrations (MICs) varying from 2 to 441.5±5.66 mg/ml. A synergistic interaction was obtained between amoxicillin-clavulanic acid and T. algeriensis EO against two strains of K. pneumoniae ESBL. These results demonstrate the potential of our EOs to inhibit multi-resistant pathogenic ESBL strains, as well as their synergistic interaction with antibiotics used in therapy, which could be an alternative to the use of antibiotics alone in treatment to fight against these multi-resistant pathogenic bacteria.